Numeration ability of junior high school students in solving numeration problems algebra material - Falentine Handiani Fitri; Kiki Nia Sania Effendi (Universitas Sarjanawiyata Tamansiswa, 2023)
This research is a qualitative descriptive research conducted to describe the completion of numeracy problems and determine the level of numeracy ability of junior high school students. The subjects in this study were 34 students who were grade VIII junior high school students in Ciledug District. The research instrument is a written test with three numeracy ability test description questions where each question contains three indicators of numeracy ability. The results showed that the numeracy ability of junior high school students was still classified as low, because there were 19 students who were only able to meet a maximum of one numeracy ability indicator. The percentage of numeracy ability test acquisition is 11.76% of students in the high category, 32.35% of students in the medium category, and 55.88% of students have low numeracy ability.